Strategi Pengembangan Ekowisata Mangrove Kecamatan Pariaman Utara Provinsi Sumatera Barat - Febrina Hanum; Yusni Ikhwan Siregar; Ridwan Manda Putra (Pelantar Press, 2023)
This study aims to analyze the composition of mangroves, the structure of the mangrove community, and analyze the suitability of the mangrove ecotourism area. As well as analyzing the strategy of developing ecotourism areas in the Apar Pariaman Mangrove Park. The method used in this study is a survey method with a qualitative and quantitative descriptive approach. The results showed that the Apar Mangrove Park area had a mangrove composition consisting of 5 true mangrove species, namely Rhizophora mucronata, Rhizophora apiculata, Sonneratia caseolaris, Thespesia Populnea, Acanthus illicifolius, and Nypa fruticans and 2 associated species, namely Dolichandrone spathaceatigillarium, and Oncosperma. The total density at station I is 2,400.44 ind/ha, station II is 2,611.11 ind/ha and station III the total density value is 2,811.11 ind/ha. The results of the analysis of the suitability of the mangrove ecotourism area in the Apar Mangrove Park area. The category (S1) 86.84% is very suitable. Through a SWOT analysis approach. There are two priority strategies in the development, namely (1) Maximizing strategic locations and providing good service. (2) Carry out more promotions by utilizing strategic locations through social media.